PENGEMBANGAN E-MODUL INTERAKTIF PADA MATERI PELAKU KEGIATAN EKONOMI SEBAGAI PENDUKUNG BAHAN AJAR KEMANDIRI SISWA - dika arfin isnaini (FKIP Unswagati, 2022)
AbstractThe problems contained in learning at SMAN 1 Dsidoarjo about the difficulty of students understanding the material. With the Covid-19 pandemic, the need fpr a teaching material for students in order to be able to better understand the materials provided by teachers such as Electronic Module teaching materials or often called E-modules developed using the Flipbook Application. With that the learning process will be more maximal. This research uses a Research and Development research model designed with a 4-D model (four D-Models, there are 4definition planning (design), development (development), deployment (dessiminate). Rith this teaching material is expected to later be trialled on a wider scale. The subjects of this study amounted to 36 students at positive impact on student understanding and learning autcomes.Keywords: Teaching Materials, Flipbook-based E-modules, understanding the material, student independence